A retrospective analysis on yak mortality with special emphasis on neonatal mortality - BERA, A K; MAJI, C; HUSSAIN, M; BAM, J; BHATTACHARYA, D; MAITI, SANJIT; BISWAS, T K; DEORI, S; DEB, S M (The Indian Journal of Animal Sciences, 2015)
The study was conducted to find out the mortality pattern of yak and yak calf under semi-intensive management system of rearing in different seasons. Our investigation was carried out based on clinical history, treatment record and post mortem findings of yaks maintained at the institute. Analysis of data for 11 years revealed that total herd strength varies from 87 to 209 numbers. Overall mortality of yak was highest in 2003 (23.15%) and lowest (3.23%) in 2006. Further, calf mortality was highest (21.62%) in 2009 followed by 2008 (20.4%), 2002 (16.67%), 2010 (16.28%) and 2003 (16%). Within the 11-year tenure total numbers of calf death from the farm was 54, which includes 46.3% male and 53.7% female. Out of which 37.03% mortality was observed within first month of age followed by 33.33% in 1-3 months of age. Season-wise mortality pattern was also recorded in the study. The highest mortality in respect to both overall yak mortality (47.16%) and calf mortality (48.15%) was in summer (June- August) followed by autumn (September- November) i.e. 32.95 and 38.89%, respectively. The higher rate of mortality may be one of the major reasons behind the reduced population of yak in India. Seasonal influence also has role on occurrence of yak diseases and mortality.